305 A rare case of borderline brenner tumor. (18th September 2019) - Kamino, Y; Egawa-Takata, T; Otoshi, A; Fukuda, Y; Tokugawa, Y; Nakagawa, M; Tsukahara, C; Miyatake, T; Yoshioka, H; Tsujimoto, M; Nishio, Y
Abstract : Objectives: To report a case of borderline Brenner tumor Methods: Case report and literature review Results: A 70-year old woman had lower abdominal pain and was found to have a large tumor in the pelvic cavity which had both cystic and solid leisions by ultrasonography and MRI. We underwent a surgery of total hysterectomy, bilateral salpingo-oophorectomy, omentum resection, pelvic and para-aortic lymph node dissection according to a frozen section diagnosis of borderline or malignant tumor of the ovary. The final pathological diagnosis was borderline Brenner tumor, StgaeIC3, which shows an exuberant papillary transitional cellular component with mild nuclear atypia lined by mucinous columnar epithelium without invasion to the stroma. There is no recurrent and metastasis at postoperative 3 months. Conclusions: Borderline Brenner tumor of the ovary is a rare tumor, which has only about 30 case reports of published English literatures. At present, we don't have enough knowledge about the characteristics of the tumor to decide appropriate treatment. Additional collection of data of this tumor is necessary to establish diagnosis and treatment.